Milk yield and composition of dairy sheep grazing teff or sorghum-sudangrass under Mediterranean summer conditions - Primi, Riccardo; Bernabucci, Gloria; Evangelista, Chiara; Boselli, Carlo; Napoli, Francesco; Spina, Raffaello; Bernabucci, Umberto; Ronchi, Bruno; Danieli, Pier Paolo (Frontiers in Animal Science, 2025)
Summer forage scarcity is a major constraint for Mediterranean dairy sheep farming, where high temperatures and drought reduce pasture yield and quality, leading to strong milk seasonality. Teff (Eragrostis tef (Zucc.) Trotter), a C4 annual grass native to Ethiopia, is drought- and heat-tolerant and may represent an alternative to traditional summer forages such as sorghum-sudangrass (Sorghum bicolor (L.) Moench subsp. sudanense). This study evaluated the effects of grazing teff on milk yield and composition in lactating Sarda ewes compared with sorghum-sudangrass under Mediterranean summer conditions. Thirty-two primiparous ewes in late lactation (150 ± 10 DIM) were assigned to two balanced groups (n = 16) and grazed 4 h/day for six weeks (two adaptation, four experimental) on either teff (GT) or sorghum-sudangrass (GS) pastures, supplemented with ad libitum hay and 0.5 kg/day concentrate. Pasture and milk were sampled weekly for chemical and quality analyses. Teff showed higher dry matter (30.8 vs 22.4%), crude protein (14.8 vs 10.6% DM), and ether extract (2.5 vs 1.9% DM), and lower acid detergent fiber (33.1 vs 37.4% DM) and lignin (4.1 vs 5.6% DM) compared with sorghum-sudangrass (P < 0.01). Ewes grazing teff produced slightly less milk (0.86 ± 0.09 vs 0.93 ± 0.11 kg/day; P < 0.05), with lower fat (6.19 vs 6.68%; P < 0.001) but higher lactose content (5.37 vs 5.28%; P < 0.05). Protein (5.60 vs 5.59%), somatic cell count (<200 × 10³ cells/mL), and coagulation traits were unaffected. Overall, both forages adequately supported lactating ewes during the summer. Teff appears promising for water-limited areas due to its heat and drought tolerance and stable nutritional profile, though its slightly lower voluntary intake may limit milk yield. Further studies addressing palatability and intake behavior are warranted.